The Role of Estrogen in the Modulation of Autologous Fat Graft Outcomes. Issue 1 (January 2015) - Bills, Jessica D.; Derderian, Christopher; Barker, Jenny; Lowe, Alysia; Lavery, Lawrence A.; Davis, Kathryn E.
Abstract : Background: Autologous fat grafting is a widely used procedure, yet the mechanisms that regulate graft outcomes are poorly understood. Estrogen signaling is a potent regulator of lipid handling, inflammation, fibrosis, and adipocyte progenitor recruitment in adipose tissues. To date, no studies have investigated the effect of circulating estrogens on fat graft outcomes. Methods: Immunosuppressed (Nu/Nu) mice underwent ovariectomy or sham surgery. Forty-five days later, half the mice (donors) were killed, and adipose tissue was taken and transplanted into the remaining cohort (recipients). Forty-five days after transplantation, grafts were dissected, weighed, and assessed for expression of vascular endothelial growth factor, estrogen receptor-α, and vascular density. Results: Grafts harvested from and transplanted into sham environments are smaller but more highly vascularized compared with ovariectomy environments. The estrogenic effects on grafts are more critical at the site of the donor tissue than the recipient. Finally, expression of estrogen receptor-α in the grafted tissue correlates with the observed graft characteristics, which is altered by both the donor and recipient environments. Conclusions: Circulating estrogens have significant effects on fat graft outcomes, primarily at the site of the donor tissue. As there are well-established depot-specific estrogenic responses, the choice of adipose depot used as a donor for fat grafting may affect outcomes. In addition, outcomes may be confounded by the patient's hormonal status. Understanding the mechanisms by which estrogen signaling regulates graft outcomes is important in refining this commonly used clinical procedure.